2018
DOI: 10.1080/19463014.2018.1495089
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge disagreement formulations in problem-based learning tutorials: balancing pedagogical demands with ‘saving face’

Abstract: This project is funded by The Engineering and Physical Sciences Research Council Award (EPSRC Reference 1827113). The authors would like to thank the manuscript reviewers for their attention to detail and for such supportive comments throughout the publication process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…the misalignment between what they already know, and the requirements of the problem to be solved) (De Grave, Boshuizen & Schmidt, 1996), and it is through their debates with one another that rich knowledge stances are acquired, and deeper learning occurs in arriving at successful solutions (Aarnio et al, 2013). Recent interactional research involving PBL in engineering has shown how students -even in the absence of the tutor -exhibit effective self-management strategies during knowledge disagreements (McQuade, Wiggins, Ventura-Medina & Anderson, 2018), which reaffirms the point that students must be given the educational freedom to negotiate these critical discussions themselves. Therefore, if the openended nature of PBL is to be sustained, new PBL tutors must be sufficiently supported in making the transition towards facilitator of student-centred learning (Azer, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…the misalignment between what they already know, and the requirements of the problem to be solved) (De Grave, Boshuizen & Schmidt, 1996), and it is through their debates with one another that rich knowledge stances are acquired, and deeper learning occurs in arriving at successful solutions (Aarnio et al, 2013). Recent interactional research involving PBL in engineering has shown how students -even in the absence of the tutor -exhibit effective self-management strategies during knowledge disagreements (McQuade, Wiggins, Ventura-Medina & Anderson, 2018), which reaffirms the point that students must be given the educational freedom to negotiate these critical discussions themselves. Therefore, if the openended nature of PBL is to be sustained, new PBL tutors must be sufficiently supported in making the transition towards facilitator of student-centred learning (Azer, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…The trainee responds to his suggestions by referring to the external source again: she repeats that she has checked the specific guidelines (lines 43‐47) and it says ‘just ordinary benzos’. By bringing up the guideline, the trainee appears to be appealing to an external authority and thus minimising the disagreement 42 . In the end, supervisor and trainee do not align; the trainee ultimately states that it's unnecessary to consult these specialists because they will reach the same conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…By bringing up the guideline, the trainee appears to be appealing to an external authority and thus minimising the disagreement. 42 In the end, supervisor and trainee do not align; the trainee ultimately states that it's unnecessary to consult these specialists because they will reach the same conclusion. In this example, we see that ignoring the trainee's expressed knowledge by immediately suggesting alternatives prevents a knowledge exchange in which trainee and supervisor come to a shared decision or a general consensus on which knowledge is decisive, the medical guidelines or practical experience.…”
Section: Resultsmentioning
confidence: 99%
“…There are a host of well documented difficulties in ensuring that every member of a team reaches the same learning outcomes during group work. [ 26,27 ] In this course format, this is accentuated, and both student‐reported and anecdotal evidence suggests that in some groups a subset of students take on the experimental design and decision‐making tasks, while other members take care of the more familiar aspects of the deliverables, thus bypassing most open‐ended course design elements and benefits. This causes an imbalance in the level to which each student benefits from this experience, which requires active participation to get the most out of it.…”
Section: Challengesmentioning
confidence: 99%